BADIIY ONIMLARNING KONNOTATIVLIK XUSUSIYATLARI - Baxtiyorova, M. (SCIENCE and SOCIETY, 2023)
Recently, many studies have been conducted in linguistics, which consider language not only as a means of communication, but as a cultural indicator of the nation. Such studies are based on the idea that the most subtle aspects of the people's culture are manifested in its unique language. Based on such approaches, language requires an analysis of not only the modern mentality of the nation, but also the thoughts of the people of the past times about the world, society, and themselves. The article reveals the linguistic and cultural features of the onomasticons given in the literary works.
Keywords: cultural linguistics; proper noun; literary onomasticon; connotation; culture